Transient response analysis of anisotropic solids with nano‐cavities by BEM. Issue 4 (2nd November 2020) - Parvanova, Sonia; Dineva, Petia
Abstract: Тwo‐dimensional in‐plane transient elasto‐dynamic problem for isotropic/anisotropic, finite/infinite solids with nano‐cavities is formulated. The mechanical model combines: (a) classical elastodynamic theory for the bulk anisotropic solid; (b) non‐classical boundary conditions and localized constitutive equation for the interface between nano‐cavities and anisotropic matrix within the frame of the Gurtin‐Murdoch surface elasticity theory. The computational approach uses Fourier‐domain BEM (boundary element method) in conjunction with closed form frequency dependent fundamental solution. Accuracy and convergence of the numerical solutions for dynamic stress concentration factor (DSCF) and scattered wave field displacements is studied by comparison with available solutions. In addition a parametric study for the transient wave field sensitivity in bounded and unbounded solids to the type and characteristics of the transient disturbance, to the surface elasticity phenomena, to the nano‐cavities interaction and to the type of the material anisotropy is presented. Abstract : Тwo‐dimensional in‐plane transient elasto‐dynamic problem for isotropic/anisotropic, finite/infinite solids with nano‐cavities is formulated. The mechanical model combines: (a) classical elastodynamic theory for the bulk anisotropic solid; (b) non‐classical boundary conditions and localized constitutive equation for the interface between nano‐cavities and anisotropic matrix within the frame of the Gurtin‐Murdoch surface elasticity theory. The computational approach uses Fourier‐domain BEM (boundary element method) in conjunction with closed form frequency dependent fundamental solution….